(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Aphids are the most important pests on wheat in Egypt and worldwide. Field trials were conducted to assess the efficacy of the neonicotinoid insecticides imidacloprid (Nufidor 60% FS; at the doses of 2.1, 1.05 and 0.525 g a.i./kg of seeds) and thiamethoxam (Cruiser 70% WS; at the rates of 14.4, 7.2 and 3.6 g a.i./kg of seeds) as seed treatments, and thiamethoxam (Actara 25% WG; at the rates of 0.1, 0.05 and 0.025 g a.i./l) as foliar application, against three wheat aphids: bird cherry oat aphid, Rhopalosiphum padi (L.), greenbug, Schizaphis graminum (Rondani), and corn leaf aphid, Rhopalosiphum maidis (Fitch). Their effects on the aphids’ natural enemies: lacewings, Chrysoperla carnea Stephens, ladybird beetles, Coccinella spp., and syrphid flies Syrphus spp. were assessed as well. The trials were conducted on the farm of the Faculty of Agriculture, Suez Canal University, Ismailia Governorate, during 2013/14 and 2014/15 seasons. Our results showed significant differences between the tested insecticides at all concentrations and clearly indicated that the recommended doses of all insecticides were more efficient against aphids on wheat plants than half- and quarter-doses. Also, the data revealed significant differences between the two seed treatments at all doses before and after foliar application, as compared to the control at all time intervals of inspection regarding the mean number of aphids on wheat plants, from the 3rd until 13th week after sowing, except in the 8th week after seed treatment before foliar application. The results clearly indicated that the weekly reduction of infestation and the general efficacy was higher at the recommended doses of Nufidor, Cruiser and Actara than the half and quarter doses in both seasons. Also, reduction in infestation decreased over the following weeks until the 8th week, when Actara insecticide was sprayed. Data revealed that there were no significant differences between treatments and control in the mean number of Chrysoperla carnea and Syrphus spp., while a significant difference in the mean number of coccinellids was observed on wheat plants treated with imidacloprid seed treatment before foliar application 6 and 7 weeks after sowing, and also after foliar application with thiamethoxam 9, 10, 11, 12 and 13 weeks after sowing. Regarding thiamethoxam seed treatment, significant differences were revealed in the ladybird population on wheat plants 3, 4, 7 and 8 weeks before foliar application, and only in the 10th week after spraying with thiamethoxam.